SEGMENTATION OF FOOD SHOPPERS IN TURKEY: AN APPLICATION OF FOOD-RELATED LIFESTYLE INSTRUMENTS - ÇOBANOĞLU, EMİNE (FUTURE ACAD, 2017)
Market segmentation divides the market into small groups of consumers who share similar characteristics, and the life style segmentation has become one of the ideal criteria to segment the market. In this study, the food-related lifestyle (FRL), was used to segment the food shoppers in Istanbul in order to understand the different market segments and their food consumption behaviour, as FRL is one of the most elaborate food segmentation tools and proven to be cross-culturally suitable and valid. The present study serves as one of the first attempts to employ the FRL instrument to explore food-related lifestyle segments in Turkey. Data was collected using an online survey utilizing a questionaire with variables adapted from the FRL. Cluster analysis was used to segment food shoppers into four FRL groups: Rational consumers (31.4 %) who are very organised in shopping and cooking for food; food focus consumers (25.4%) who pay attention every single aspect of food; careless (24.7) consumers who care less most of the food-related activities and mostly consist of consumers aged between 18-25; and uninvolved (18.5%) are not active in food-related activities. Research findings could serve as a reference for local and international food companies to develop marketing strategies. (C) 2017 Published by Future Academy www.FutureAcademy.org.uk
Keywords: Segmentation; Food-related life style; Food consumption; Cluster analysis; MEAT CONSUMPTION; GREAT-BRITAIN; CONSUMER; ORIENTATION; ATTITUDES; QUALITY; VALUES